MULTI-RESPONSE OPTIMIZATION ON ABRASIVE WATERJET MACHINING OF GLASS FIBER REINFORCED PLASTICS USING TAGUCHI METHOD COUPLED WITH TOPSIS - Shanmugam, A.; Mohanraj, T.; Krishnamurthy, K.; Gur, Ali Kaya (World Scientific Publ Co Pte Ltd, 2021)
This work aims to perform the multi-response optimization for abrasive waterjet machining (AWJM) of glass fiber reinforced plastics (GFRP). The experiments were conducted with AWJM factors like pressure (P), traverse speed (TS), and standoff distance (SOD) at three levels. Taguchi's L-9 orthogonal array (OA) was used to design the experiments. The influence of control factors was evaluated by measuring the surface roughness and taper angle while cutting GFRP. The optimum parameter for an individual response was obtained through Taguchi's S/N and multi-response optimization was performed with TOPSIS. From TOPSIS, the optimal parameter of the pressure of 200 MPa, standoff distance (SOD) of 1.5 mm, and traverse speed (TS) of 25 mm/min were found. After optimization, the taper angle was decreased by 1.41%. The influence of cutting variables on the responses was statistically analyzed through analysis of variance. It was observed that the pressure has a significant effect on multi-response characteristics and a contribution of 85.90%. After, AWJM, the surface was examined using SEM analysis and found the deformation and pull-out of fibers.
Keywords: Abrasives; pressure; standoff distance; traverse speed; glass fiber reinforced plastics; surface roughness; kerf width; taper angle; Taguchi; TOPSIS